The lack of torus emission from BL Lacertae objects: An infrared view of unification with WISE - Plotkin, Richard; Anderson, S.; Brandt, W.; Markoff, S.; Shemmer, O.; Wu, J. (Institute of Physics Publishing, 2012)
We use data from the Wide-Field Infrared Survey Explorer (WISE) to perform a statistical study on the mid-infrared (IR) properties of a large number (102) of BL Lac objects - low-luminosity active galactic nuclei (AGNs) with a jet beamed toward the Earth. As expected, many BL Lac objects are so highly beamed that their jet synchrotron emission dominates their IR spectral energy distributions. In other BL Lac objects, however, the jet is not strong enough to completely dilute the rest of the AGN emission. We do not see observational signatures of the dusty torus from these weakly beamed BL Lac objects. The lack of observable torus emission is consistent with suggestions that BL Lac objects are fed by radiatively inefficient accretion disks. Implications for the "nature versus nurture" debate for FR I and FR II radio galaxies are briefly discussed. Our study supports the notion that, beyond orientation, accretion rate plays an important role in AGN unification.